2009
DOI: 10.1007/s10886-008-9577-1
|View full text |Cite
|
Sign up to set email alerts
|

The Chlorophyll Catabolite, Pheophorbide a, Confers Predation Resistance in a Larval Tortoise Beetle Shield Defense

Abstract: Larval insect herbivores feeding externally on leaves are vulnerable to numerous and varied enemies. Larvae of the Neotropical herbivore, Chelymorpha alternans (Chrysomelidae:Cassidinae), possess shields made of cast skins and feces, which can be aimed and waved at attacking enemies. Prior work with C. alternans feeding on Merremia umbellata (Convolvulaceae) showed that shields offered protection from generalist predators, and polar compounds were implicated. This study used a ubiquitous ant predator, Azteca l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…It was proposed that these proteins utilize bound chlorophyllide for antibacterial and antiviral activities of the larva (Pandian et al, 2008). Interestingly, tortoise beetle larvae have evolved to utilize pheophorbide a as a deterrent in a fecal shield to protect themselves from their predators (Vencl et al, 2009). A defensive compound could have contrasting effects against different insect species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that these proteins utilize bound chlorophyllide for antibacterial and antiviral activities of the larva (Pandian et al, 2008). Interestingly, tortoise beetle larvae have evolved to utilize pheophorbide a as a deterrent in a fecal shield to protect themselves from their predators (Vencl et al, 2009). A defensive compound could have contrasting effects against different insect species.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that organisms use the toxicity of tetrapyrroles for their defense systems. The larvae of tortoise beetle (Chelymorpha alternans) even utilize pheophorbide a as a powerful deterrent in the fecal shield to protect themselves from their predators (Vencl et al, 2009). Kariola et al (2005) suggested that a chlorophyll derivative, chlorophyllide, is involved in the defense against fungi, based on their observations that down-regulation of a chlorophyllhydrolyzing enzyme, chlorophyllase (CLH), results in increased susceptibility of Arabidopsis (Arabidopsis thaliana) plants to the necrotrophic fungus Alternaria brassicicola.…”
mentioning
confidence: 99%
“…Because they both feed on the same host plant, Merremia umbellata (Convolvulaceae), their larvae confront the same enemies as they graze openly on leaves (e.g., Windsor et al 1992;Cuignet et al 2008). The larvae of both species have an unpalatable defense in the form of a physical and chemical barrier, or shield, which is mobile and fortified with host-derived chemicals (Vencl et al 2005(Vencl et al , 2009). Only A. sparsa employs a maternal care defense tactic, wherein females guard their offspring from egg until adult emergence (Windsor 1987).…”
Section: Communicated By M Elgarmentioning
confidence: 99%
“…Alternatively, endophytes may have made A. sparsa larvae less repellent by interfering with their production of defensive chemical compounds. The closely related tortoise beetle Chelymorpha alternans (Boheman) metabolises M. umbellata-derived chlorophyll in its gut to the catabolite pheophorbide a, which has been shown to deter A. lacrymosa ants in bioassays similar to those presented here (Vencl et al, 2009). Perhaps secondary metabolites particular to, or elevated in, E high leaves (Petrini et al, 1992) reduced the ability of the beetle larvae to convert chlorophyll to defensive chemical compounds, resulting in higher ant predation without necessarily having an effect on herbivore performance.…”
Section: Resultsmentioning
confidence: 52%
“…Trials began when an ant first antennated the larva, and were separated by 3 min to maximise independence by increasing the likelihood that different ants would be tested in each trial. We baited the platform with tuna 1 h prior to the first trial to ensure colony feeding motivation (Vencl et al, 2009); the ants' response to the bait and the thawed larvae was generally similar.…”
Section: Methodsmentioning
confidence: 99%